2015
DOI: 10.1002/14651858.cd011737
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in saturated fat intake for cardiovascular disease

Abstract: The findings of this updated review are suggestive of a small but potentially important reduction in cardiovascular risk on reduction of saturated fat intake. Replacing the energy from saturated fat with polyunsaturated fat appears to be a useful strategy, and replacement with carbohydrate appears less useful, but effects of replacement with monounsaturated fat were unclear due to inclusion of only one small trial. This effect did not appear to alter by study duration, sex or baseline level of cardiovascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
445
5
28

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(502 citation statements)
references
References 583 publications
24
445
5
28
Order By: Relevance
“…Among the suggested mechanisms are factors that alter the lipid/lipoprotein profile, such as inactivating sterol regulatory element binding protein (SREBP), a transcription factor that regulates cholesterol synthesis, and increasing expression of hepatic LDL receptor via stimulating acyl-CoA: cholesterol acyltransferase 7 …”
Section: Replacing Dairy Fat With Pufa and Carbohydratementioning
confidence: 99%
“…Among the suggested mechanisms are factors that alter the lipid/lipoprotein profile, such as inactivating sterol regulatory element binding protein (SREBP), a transcription factor that regulates cholesterol synthesis, and increasing expression of hepatic LDL receptor via stimulating acyl-CoA: cholesterol acyltransferase 7 …”
Section: Replacing Dairy Fat With Pufa and Carbohydratementioning
confidence: 99%
“…Metaanalyser av randomiserte kontrollerte studier Fem metaanalyser undersøkte effektene av å redusere inntaket av mettet fett i randomiserte kontrollerte studier med hjerte-og karsykdom som endepunkt 126,127,[148][149][150] . To av disse hadde spesielt fokus på et redusert inntak av mettet fett til fordel for flerumettet fett 127,148 .…”
Section: Mettet Fett Og Risiko For Hjerte-og Karsykdomunclassified
“…To av disse hadde spesielt fokus på et redusert inntak av mettet fett til fordel for flerumettet fett 127,148 . Tre metaanalyser undersøkte effekten av både generell fettreduksjon og effektene av et «modifisert» fettinntak, med mindre mettet fett 126,149,150 . Antall inkluderte studier i metaanalysene varierte fra 7 til 48.…”
Section: Mettet Fett Og Risiko For Hjerte-og Karsykdomunclassified
See 1 more Smart Citation
“…The Grading of Recommendations Assessment, Development and Evaluation (GRADE) is one useful approach to help evaluate the literature [26]. Using GRADE in evaluating RCTs Hooper et al found ‘moderate’ quality evidence for the recommendation to replace SFA with polyunsaturated fats [27]. In observational studies, de Souza et al found the evidence for a lack of association between SFA and CVD to be ‘very low’ [5].…”
Section: Introductionmentioning
confidence: 99%